Application Of Design Thinking Method For Ui And Ux Design In Ngajiyuk - Fattya Ariani; Andi Taufik; Atifah Arsanti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Learning at home during the Covid outbreak has more or less become an obstacle for children, so parents are required to participate in the learning process, one of which is by learning the Qur'an. The purpose of this study is to create new media that makes it easier for teachers to assess and receive payments easily by designing the User Interface display and User Experience of the study application that makes it easy and interesting for students, teachers, and parents by using metode design thinking which has several processes , namely emphasize, define, ideate, prototype, and test on the user. Based on the results of research that has been carried out, it can be concluded that the design of the appearance of the NgajiYuk application attracts interest in learning to study children, helps make iteasier for teachers to provide learning materials and conduct learning assessments, and makes it easier for parents to monitor children's learning outcomes